Principales desafíos de la presidencia de Al Sisi en Egipto: Seguridad, reactivación económica y reformas - González del Miñp, Paloma (Nómadas. Critical Journal of Social and Juridical Science, 2015)
The three years of the political transition in Egypt show a difficult and very open scenario with a questionable balance on the political level and a deep economic crisis. The victory of Al-Sisi, after clearing the other most powerful political force since the rebellions of January 2011, that is the Muslim Brotherhood, proves the commitment to security, economic recovery and reform, the three principal axes of the weak electoral program of the president. This “guided transition” by military forces cannot hide the challenges faced by the country. In this logic, the actions of Al-Sisi are focused in national politics whose substantive challenges can squander his presidency, delaying the permanent Egyptian aspiration of being regarded as the natural leader of the Arab world.